Thermo-Mechanical Process-Induced Residual Stresses and Deformation Analysis During Manufacturing of Hull Structure - Saad Ahmed; Muhammad Asif; Asad Ali Zaidi (Memoria Investigaciones en Ingeniería)
Hull structures such as stiffened plates and thin panels are the building blocks of ship structures, and therefore understanding their manufacturing process is of utmost importance. The welding process has been widely used to join stiffeners, stringers, and girders onto the plate. The thermo-mechanical loading and constraints during the welding process generally induced deformations and residual stresses. A deep understanding of the process parameters during thermo-mechanical processing is required to control the process-induced deformation. Therefore, this study aims to investigate the deformation and thermal stress generation in hull structures (panels/stiffened plates) during thermo-mechanical processes such as welding. A finite element modeling approach was proposed while incorporating the thermal and nonlinear thermo-elastic-plastic material behavior. The thin panels with different geometrical configurations and boundary conditions were simulated using steady state and transient heat-transfer-stress deformations analysis to simulate real-life scenarios. Both modeling approaches give a useful insight into understanding the complex nature of deformation and built-up residual stresses. However, the transient heat transfer-stress deformation analysis results were found in a reasonably good agreement with experimental data.